(untitled) (Scientific journal of the Fergana State University, 2023)
The colourful traditions of Uzbek people are unusual. It is impossible to enumerate the incomparable traditions and customs that are passed down from year to year, from generation to generation. But there are still such customs that seem much more harmful than being useful. Several Uzbeks, who expressed their opinion in the survey, suggested that these customs should be abandoned. However, they especially emphasized that they are proud of certain traditions and that they like them very much.